Improving the Performance of MIMO Fading Channel Simulators Using New Parameterization Method: تحسين أداء نموذج محاكاة الخفوت للأقنية MIMO باستخدام خوارزميات جديدة لحساب المعاملات - Omar Yousuf Alzoubi (Journal of engineering sciences and information technology, 2020)
The research aims to modeling and simulation of fading channels for providing necessary tool to develop communication systems. The modeling and simulation of MIMO fading channels is studied for both isotropic- and non-isotropic scattering cases for one-ring model, so in this context, three methods for MIMO simulation channel models are studied: Extended Method of Exact Doppler Spread (EMEDS), Modified Method of Equal Areas (MMEA) and Method Lp-Norm (LPNM). Three new methods are also suggested to design the simulation model of MIMO channel: Modified Extended Method of Exact Doppler Spread (MEMEDS), New Modified Method of Equal Areas (NMMEA) and Modified Lp-Norm method (MLPNM). The performance of each proposed method is compared with the original method by comparing the statistical properties ACF, 2D-CCF and CF of both reference and simulation models.